2015
DOI: 10.1111/acv.12185
|View full text |Cite
|
Sign up to set email alerts
|

Setting evolutionary‐based conservation priorities for a phylogenetically data‐poor taxonomic group (Scleractinia)

Abstract: Given the current extinction crisis coupled with the shortfall in funding, there is a pressing need to establish species conservation priorities. The prioritization of phylogenetic diversity and evolutionary distinctiveness is one approach; however, taking such an approach requires more phylogenetic data than are currently available for most taxa. Here, we investigate the effects of increased phylogenetic knowledge on the accuracy of evolutionary distinctiveness (ED) scores over time using scleractinian corals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 77 publications
1
52
0
Order By: Relevance
“…Therefore, these genes are more informative for reconstructing deep coral phylogenies. Other than the 16S rDNA that established widespread subordinal non-monophyly Palumbi 1996, 1997;Le GoffVitry et al 2004), 12S rDNA, cytochrome b and cytochrome c oxidase subunit I (COI) were purposed for corals relatively early (Medina et al 1999;van Oppen et al 1999;Fukami et al 2000) and have been used for inferring large scleractinian trees effectively (Chen et al 2002;Fukami et al 2004bFukami et al , 2008Barbeitos et al 2010;Kitahara et al 2010bKitahara et al , 2013Stolarski et al 2011;Arrigoni et al 2012Arrigoni et al , 2014cHuang 2012;Huang andRoy 2013, 2015;Marcelino et al 2013;Curnick et al 2015; Fig. 4.1).…”
Section: The Rise Of Molecular Phylogenetic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these genes are more informative for reconstructing deep coral phylogenies. Other than the 16S rDNA that established widespread subordinal non-monophyly Palumbi 1996, 1997;Le GoffVitry et al 2004), 12S rDNA, cytochrome b and cytochrome c oxidase subunit I (COI) were purposed for corals relatively early (Medina et al 1999;van Oppen et al 1999;Fukami et al 2000) and have been used for inferring large scleractinian trees effectively (Chen et al 2002;Fukami et al 2004bFukami et al , 2008Barbeitos et al 2010;Kitahara et al 2010bKitahara et al , 2013Stolarski et al 2011;Arrigoni et al 2012Arrigoni et al , 2014cHuang 2012;Huang andRoy 2013, 2015;Marcelino et al 2013;Curnick et al 2015; Fig. 4.1).…”
Section: The Rise Of Molecular Phylogenetic Methodsmentioning
confidence: 99%
“…With more markers available for inferring phylogenies, combined analyses of multilocus data may be the way forward. Recent large-scale studies (>450 species) have sought to concatenate data from seven or more loci (Huang 2012;Huang andRoy 2013, 2015;Curnick et al 2015;Fig. 4.1).…”
Section: The Rise Of Molecular Phylogenetic Methodsmentioning
confidence: 99%
“…Toh et al (2014) showed that while labour and equipment contributed significantly to the cost of producing sexually propagated corals for transplantation, greater economies of scale could be achieved by introducing feeds to augment coral growth during the nursery phase. Additionally, factors such as the evolutionary distinctiveness or vulnerability of a species to global extinction can be considered when prioritising corals for restoration (Curnick et al, 2015;Huang and Roy, 2015), to supplement broad-based proxies such as site-specific species rarity.…”
Section: Incorporation Of Novel Techniques Into Restoration Designmentioning
confidence: 99%
“…Missing species and poor phylogenetic resolution have been identified as causes of uncertainty when calculating ED (Isaac et al ., ), but we were unable to find a quantitative assessment of how missing species might affect ED values of species for which data are available. Empirically in corals and gymnosperms, incomplete phylogenies produced results similar to later, more complete trees (Curnick et al ., ; Forest et al ., ). Our results support this finding.…”
Section: Discussionmentioning
confidence: 99%